Using IL‐2R/lymphocytes for predicting the clinical progression of patients with COVID‐19. (15th May 2020) - Hou, H.; Zhang, B.; Huang, H.; Luo, Y.; Wu, S.; Tang, G.; Liu, W.; Mao, L.; Mao, L.; Wang, F.; Sun, Z.
Summary: Effective laboratory markers for the estimation of disease severity and predicting the clinical progression of coronavirus disease‐2019 (COVID‐19) is urgently needed. Laboratory tests, including blood routine, cytokine profiles and infection markers, were collected from 389 confirmed COVID‐19 patients. The included patients were classified into mild ( n  = 168), severe ( n  = 169) and critical groups ( n  = 52). The leukocytes, neutrophils, infection biomarkers [such as C‐reactive protein (CRP), procalcitonin (PCT) and ferritin] and the concentrations of cytokines [interleukin (IL)‐2R, IL‐6, IL‐8, IL‐10 and tumor necrosis factor (TNF)‐α] were significantly increased, while lymphocytes were significantly decreased with increased severity of illness. The amount of IL‐2R was positively correlated with the other cytokines and negatively correlated with lymphocyte number. The ratio of IL‐2R to lymphocytes was found to be remarkably increased in severe and critical patients. IL‐2R/lymphocytes were superior compared with other markers for the identification of COVID‐19 with critical illness, not only from mild but also from severe illness. Moreover, the cytokine profiles and IL‐2R/lymphocytes were significantly decreased in recovered patients, but further increased in disease‐deteriorated patients, which might be correlated with the outcome of COVID‐19. Lymphopenia and increased levels of cytokines were closely associated with disease severity. The IL‐2R/lymphocyte was a prominent biomarker for early identification of severe COVID‐19 and predicting the clinical progression of the disease. Abstract : IL‐2R/lymphocyte was a superior marker for the identification of severe COVID‐19 patients.